HALOALKALIPHILIC BACILLUS FLEXUS AW3(2): POTENTIAL FOR BIOTECHNOLOGICAL APPLICATIONS - VISHAL R DHUNDALE; VIJAYSHREE M HEMKE; VRUSHALI R MORE; RACHANA D NAGARKAR (International Journal of Pharma and Bio Sciences, 2015)
The traditional cultivation based methods have a great importance in research, providing the chance in investigations of biotechnologically significant bacterial isolates under in vitro. A total of one hundread and fourteen bacteria was isolated from the water and sediment samples collected from the hyperalkalinesaline environment of Lonar crater. Out of them strain AW3(2) was selected for 16S rDNA sequencing, production and, partial characterizations of amylase on the basis of their maximum amylolytic activity. A Gram positive bacterium was identified as Bacillus flexus by morphological, physiological and biochemical characterisation and 16S rDNA sequencing. The bacterium grew in sodium chloride (NaCl w/v) from 0.5 to 7% and at pH 7–12. A substantial level of extracellular alkaline amylase was produced by Bacillus flexus AW3(2). Optimum enzyme activity was found to be at 70°C (1.2 unit/mL), pH 10.0 (5.9 units/mL), and 4% NaCl. The amylase was highly stable over a broad temperature from 40 to 100°C, pH 6.0-12.0, and NaCl concentration 0.5-10% ranges, showing excellent thermostablity, and haloalkaline tolerant nature. A Lineweaver-Burk plot indicates that enzyme has a Km of 2.94 mg/mL and a Vmax of 90.90 mg/mL/ min. The enzyme activity has enhanced by BaCl2 (7.4 units/mL/min), indicating it was a metalloenzyme. Among the organic nitrogen sources, optimum amylase production was found to be in presence of yeast extract. This is valuable information for enzyme production and optimization of amylase has a bright future towards the improvement and production of novel enzymes for entirely new areas of industrial and biotechnological applications involving molecular enzymology. The developing novel techniques in genetic engineering combined with better knowledge of structure and function allow fulfillment of industrial needs and exploration of novel applications.